Silicon-carbon negative electrode material, preparation method thereof, negative electrode plate and battery
By using a combination of nano-scale coating material and porous graphene on the silicon carbon negative electrode material, a network structure and nanopore structure are formed, which solves the expansion problem of silicon carbon negative electrode material during charging and discharging, and improves the cycle stability of the battery Sex and lifespan.
Patent Information
- Application Number
- CN202411235600.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
AI Technical Summary
The silicon carbon anode material will experience severe expansion during the charging and discharging process, resulting in degradation of battery performance and safety issues. The expansion problems need to be improved to improve cycle stability and life.
Nano-scale coating materials such as carbon dioxide fiber, alumina fiber and silicon nitride fiber are used to form a network structure through chemical vapor deposition method, and porous graphene is added to the silicon carbon negative electrode material, and it is evenly distributed through physical mixing and heat treatment to form Optimized silicon-carbon negative electrode material.
It effectively reduces the expansion rate of silicon-carbon negative electrode material, maintains the stability of the electrode structure, extends the service life of the battery, and improves the circulation performance and safety of the battery.
Smart Images

Figure CN119133391A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] With the development of science and technology, lithium-ion batteries have been widely used in electric vehicles, mobile devices and other fields as efficient and environmentally friendly energy storage devices. Silicon-carbon negative electrode materials have become a hot topic of research due to their high energy density and low cost. However, silicon will expand severely during the charging and discharging process, resulting in a decrease in battery performance and even safety issues. Therefore, improving the expansion problem of silicon-carbon negative electrode materials is of great practical significance. Summary of the invention
[0003] The present invention provides a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a battery, which can reduce the expansion rate of the silicon-carbon negative electrode material and improve the cycle stability and life of the battery.
[0004] In order to solve the above technical problems, a technical solution adopted by the present invention is: to provide a method for preparing a silicon-carbon negative electrode material, comprising:
[0005] Selecting a nanoscale coating material, wherein the coating material includes at least one of carbon dioxide fiber, aluminum oxide fiber and silicon nitride fiber;
[0006] The coating material is uniformly coated on the surface of the pre-configured silicon-carbon negative electrode material by chemical vapor deposition to obtain a preliminary silicon-carbon negative electrode material with a network structure;
[0007] Porous graphene is added to the preliminary silicon-carbon negative electrode material, and through physical mixing treatment and heat treatment, the porous graphene is evenly distributed inside and on the surface of the preliminary silicon-carbon negative electrode material to obtain an optimized silicon-carbon negative electrode material, wherein the pore size of the porous graphene is 10nm-50nm.
[0008] According to one embodiment of the present invention, the step of uniformly coating the coating material on the surface of the pre-configured silicon-carbon negative electrode material by chemical vapor deposition to obtain a preliminary silicon-carbon negative electrode material having a network structure comprises:
[0009] Performing drying pretreatment on the preconfigured silicon-carbon negative electrode material;
[0010] The coating material and the pre-dried silicon-carbon negative electrode material are subjected to a chemical vapor deposition reaction to obtain a preliminary silicon-carbon negative electrode material having a network structure;
[0011] The preliminary silicon-carbon negative electrode material is post-processed.
[0012] According to one embodiment of the present invention, the drying temperature of the drying pretreatment is 100°C, and the drying time is 7 hours; the reaction temperature of the chemical vapor deposition reaction is 400°C, and the reaction time is 2-5 hours; the post-treatment is: maintaining at a temperature of 500°C for 3-5 hours.
[0013] According to one embodiment of the present invention, in the step of adding porous graphene to the preliminary silicon-carbon negative electrode material, and uniformly distributing the porous graphene inside and on the surface of the preliminary silicon-carbon negative electrode material through physical mixing treatment and heat treatment to obtain an optimized silicon-carbon negative electrode material, the heat treatment is: in an inert atmosphere, placing the mixture obtained by physical mixing treatment at a temperature of 500°C-800°C, and reacting for 6-8 hours.
[0014] According to one embodiment of the present invention, relative to the mass of the silicon-carbon negative electrode material, the mass of the coating material is 0.5wt%-1.0wt%, and the mass of the porous graphene is 10wt%-15wt%.
[0015] According to one embodiment of the present invention, the average diameter of the coating material is 50nm-500nm.
[0016] According to one embodiment of the present invention, the thickness of the network structure is 50nm-100nm, the network structure has pores, and the pore size of the porous graphene is smaller than the pore size of the pores.
[0017] In order to solve the above technical problems, another technical solution adopted by the present invention is: to provide a silicon-carbon negative electrode material, including: prepared by the preparation method of the silicon-carbon negative electrode material.
[0018] In order to solve the above technical problems, another technical solution adopted by the present invention is: to provide a negative electrode sheet containing the silicon-carbon negative electrode material.
[0019] In order to solve the above technical problem, another technical solution adopted by the present invention is: to provide a battery containing the negative electrode sheet.
[0020] The beneficial effects of the present invention are as follows: a method for preparing a silicon-carbon negative electrode material comprises: selecting a nano-scale coating material; uniformly coating the coating material on the surface of a pre-configured silicon-carbon negative electrode material by chemical vapor deposition to obtain a preliminary silicon-carbon negative electrode material with a network structure; adding porous graphene to the preliminary silicon-carbon negative electrode material, and uniformly distributing the porous graphene inside and on the surface of the preliminary silicon-carbon negative electrode material by physical mixing treatment and heat treatment to obtain an optimized silicon-carbon negative electrode material, wherein the pore size of the porous graphene is 10nm-50nm. The silicon material in the silicon-carbon negative electrode material will produce a large volume expansion during the charging and discharging process, and the network structure formed by the coating material can effectively alleviate this expansion. The nanopore structure of the porous graphene provides sufficient buffer space for the volume expansion of the silicon material during the charging and discharging process, thereby effectively reducing the expansion rate of the silicon-carbon negative electrode material, maintaining the stability of the electrode structure, and extending the service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 1 is a schematic flow chart of a method for preparing a silicon-carbon negative electrode material according to an embodiment of the present invention;
[0022] Figure 2 It is a schematic flow chart of a method for preparing a silicon-carbon negative electrode material according to another embodiment of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The terms "first", "second" and "third" in the present invention are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first", "second" and "third" can explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. All directional indications (such as up, down, left, right, front, back...) in the embodiments of the present invention are only used to explain the relative position relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication also changes accordingly. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally also includes steps or units that are not listed, or optionally also includes other steps or units inherent to these processes, methods, products or devices.
[0025] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0026] Figure 1 FIG. 1 is a flow chart of a method for preparing a silicon-carbon negative electrode material according to an embodiment of the present invention. It should be noted that if substantially the same results are obtained, the method of the present invention is not limited to the method of Figure 1 The process sequence shown is limited. Figure 1 As shown, the method comprises the steps of:
[0027] Step S10: selecting a nano-scale coating material, wherein the coating material includes at least one of carbon dioxide fiber, aluminum oxide fiber and silicon nitride fiber.
[0028] In step S10, the average diameter of the coating material is 50 nm-500 nm, preferably 50 nm-70 nm.
[0029] Step S20: uniformly coating the coating material on the surface of the pre-configured silicon-carbon negative electrode material by chemical vapor deposition to obtain a preliminary silicon-carbon negative electrode material with a network structure.
[0030] In step S20, relative to the mass of the silicon-carbon negative electrode material, the mass of the coating material is 0.5wt%-1.0wt%, preferably 0.5wt%-0.7wt%. The thickness of the network structure is 50nm-100nm, and the network structure has pores. The silicon of the silicon-carbon negative electrode material will produce a large volume expansion during the charging and discharging process, and the network structure formed by the coating material can effectively alleviate this expansion, thereby maintaining the stability of the electrode structure; in addition, the coating material itself has good electron transmission ability, and the network structure formed can improve the conductivity of the silicon-carbon negative electrode material and reduce the internal resistance of the battery; in addition, the network structure formed by the coating material can isolate the direct contact between the silicon-carbon negative electrode material and the electrolyte, reduce the occurrence of side reactions, and thus improve the cycle stability and safety of the battery.
[0031] As an example, see Figure 2 , step S20 further includes the following steps:
[0032] Step S201: performing drying pretreatment on the pre-configured silicon-carbon negative electrode material.
[0033] Specifically, the silicon-carbon negative electrode material is commercially available, and the drying temperature of the drying pretreatment is 100° C. and the drying time is 7 hours.
[0034] Step S202: subjecting the coating material and the pre-dried silicon-carbon negative electrode material to a chemical vapor deposition reaction to obtain a preliminary silicon-carbon negative electrode material having a network structure.
[0035] Specifically, the chemical vapor deposition reaction is carried out under an inert atmosphere, such as nitrogen or argon, and the reaction temperature of the chemical vapor deposition reaction is 400° C. and the reaction time is 2-5 hours.
[0036] Step S203: post-processing the preliminary silicon-carbon negative electrode material.
[0037] Specifically, the post-treatment is: maintaining the temperature at 500° C. for 3-5 hours. This step can improve the stability and performance of the network structure.
[0038] Step S30: adding porous graphene to the preliminary silicon-carbon negative electrode material, and making the porous graphene evenly distributed inside and on the surface of the preliminary silicon-carbon negative electrode material through physical mixing treatment and heat treatment to obtain an optimized silicon-carbon negative electrode material.
[0039] In step S30, the mass of porous graphene is 10wt%-15wt%, preferably 10wt%, relative to the mass of the silicon-carbon negative electrode material. Physical mixing treatments include stirring, grinding, and ultrasound. Heat treatment is: in an inert atmosphere, the mixture obtained by physical mixing treatment is placed at a temperature of 500°C-800°C and reacted for 6-8 hours. During the heat treatment, the carbon source will be carbonized to form a stable carbon matrix, and a stable interface bonding will be formed between the porous graphene and the silicon material, thereby enhancing the overall structural stability of the silicon-carbon negative electrode material.
[0040] Furthermore, the pore size of porous graphene is smaller than that of pores, wherein the pore size of porous graphene is 10nm-50nm. This pore size helps to provide sufficient space to accommodate the volume change of silicon material during charging and discharging, while maintaining the rapid transmission channel of electrons and ions, thereby effectively reducing the expansion rate of silicon-carbon negative electrode materials; in addition, the stable interface formed between porous graphene and silicon and carbon matrix enhances the overall structural stability of silicon-carbon negative electrode materials, enabling them to better resist the stress caused by volume change during the cycle; in addition, the high conductivity and porous structure of porous graphene can promote the rapid transmission of electrons and ions within the material, improving the electrochemical performance of the battery.
[0041] The preparation method of the silicon-carbon negative electrode material of one embodiment of the present invention introduces nano-scale coating materials and porous graphene by optimizing the treatment of the silicon-carbon negative electrode material, thereby effectively inhibiting the expansion of silicon during the charging and discharging process and improving the cycle performance and life of the battery; the preparation method is simple and easy, low in cost, suitable for large-scale production, and can be widely used in the manufacture of lithium-ion batteries in the fields of new energy electric vehicles, mobile devices, etc., and has broad application prospects.
[0042] An embodiment of the present invention also provides a silicon-carbon negative electrode material, which is prepared by the above-mentioned method for preparing the silicon-carbon negative electrode material. The silicon-carbon negative electrode material is optimized and nano-scale coating materials and porous graphene are introduced to effectively inhibit the expansion of silicon during the charging and discharging process, thereby improving the cycle performance and life of the battery.
[0043] The embodiment of the present invention also provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer formed on at least one side of the negative electrode current collector, wherein the negative electrode material layer contains the above-mentioned silicon-carbon negative electrode material. The negative electrode sheet introduces nano-scale coating materials and porous graphene by optimizing the silicon-carbon negative electrode material, effectively suppressing the expansion of silicon during the charge and discharge process, and improving the cycle performance and life of the battery.
[0044] The embodiment of the present invention also provides a battery, comprising a positive electrode sheet, the above-mentioned negative electrode sheet, a separator and an electrolyte, wherein the separator is configured to separate the positive electrode sheet from the negative electrode sheet. During assembly, the negative electrode sheet, the separator and the positive electrode sheet are wound to obtain a battery cell, which is then placed in a battery shell, dried, injected with electrolyte, packaged, formed and divided into different volumes to obtain a battery. The battery is obtained by optimizing the treatment of the silicon-carbon negative electrode material, introducing nano-scale coating materials and porous graphene, which effectively inhibits the expansion of silicon during the charge and discharge process, and improves the cycle performance and life of the battery.
[0045] Example 1
[0046] Preparation of silicon-carbon negative electrode materials:
[0047] Select titanium dioxide fiber with an average diameter of 50nm; dry pretreatment of the pre-configured silicon-carbon negative electrode material, the drying temperature is 100℃, and the drying time is 7 hours; chemical vapor deposition reaction is performed on the titanium dioxide fiber and the silicon-carbon negative electrode material after drying pretreatment to obtain a preliminary silicon-carbon negative electrode material with a network structure, the reaction temperature of the chemical vapor deposition reaction is 400℃, and the reaction time is 2 hours; the preliminary silicon-carbon negative electrode material is kept at a temperature of 500℃ for 3 hours; then, a porous graphene material with a pore size of 50nm is added to the preliminary silicon-carbon negative electrode material, and the porous graphene is evenly distributed inside and on the surface of the preliminary silicon-carbon negative electrode material through physical mixing treatment and heat treatment, the heat treatment temperature is 500℃, and the reaction time is 6 hours, so as to obtain an optimized silicon-carbon negative electrode material. Among them, relative to the mass of the pre-configured silicon-carbon negative electrode material, the mass of the titanium dioxide fiber is 0.5wt%, and the mass of the porous graphene is 10wt%.
[0048] Battery assembly and expansion rate test:
[0049] A negative electrode sheet is prepared by using the above silicon-carbon negative electrode material. After rolling, the thickness of the negative electrode sheet is measured with a micrometer, which is recorded as h1. A battery is assembled using the negative electrode sheet, and the battery is fully charged using an electrochemical workstation. After disassembly, the thickness of the negative electrode sheet is measured with a micrometer, which is recorded as h2. The expansion rate of the negative electrode sheet is calculated as (h2-h1) / h1×100%.
[0050] Example 2
[0051] Preparation of silicon-carbon negative electrode materials:
[0052] Select titanium dioxide fiber with an average diameter of 70nm; dry pretreatment of the pre-configured silicon-carbon negative electrode material, the drying temperature is 100℃, and the drying time is 7 hours; chemical vapor deposition reaction is performed on the titanium dioxide fiber and the silicon-carbon negative electrode material after drying pretreatment to obtain a preliminary silicon-carbon negative electrode material with a network structure, the reaction temperature of the chemical vapor deposition reaction is 400℃, and the reaction time is 2 hours; the preliminary silicon-carbon negative electrode material is kept at a temperature of 500℃ for 3 hours; then, a porous graphene material with a pore size of 50nm is added to the preliminary silicon-carbon negative electrode material, and the porous graphene is evenly distributed inside and on the surface of the preliminary silicon-carbon negative electrode material through physical mixing treatment and heat treatment, the heat treatment temperature is 500℃, and the reaction time is 6 hours, so as to obtain an optimized silicon-carbon negative electrode material. Among them, relative to the mass of the pre-configured silicon-carbon negative electrode material, the mass of the titanium dioxide fiber is 0.7wt%, and the mass of the porous graphene is 10wt%.
[0053] Battery assembly and expansion rate test:
[0054] A negative electrode sheet is prepared by using the above silicon-carbon negative electrode material. After rolling, the thickness of the negative electrode sheet is measured with a micrometer, which is recorded as m1. A battery is assembled using the negative electrode sheet, and the battery is fully charged using an electrochemical workstation. After disassembly, the thickness of the negative electrode sheet is measured with a micrometer, which is recorded as m2. The expansion rate of the negative electrode sheet is calculated as (m2-m1) / m1×100%.
[0055] Comparative Example 1
[0056] The silicon-carbon negative electrode material that has not undergone the above-mentioned optimization treatment (i.e., the pre-configured silicon-carbon negative electrode material) is made into a negative electrode sheet. After rolling, the thickness of the negative electrode sheet is measured with a micrometer, which is recorded as n1. The negative electrode sheet is used to assemble a battery, and the battery is fully charged using an electrochemical workstation. After disassembly, the thickness of the negative electrode sheet is measured with a micrometer, which is recorded as n2. The expansion rate of the electrode sheet is calculated as (n2-n1) / n1×100%.
[0057] The expansion rates of the negative electrode sheets of Examples 1-2 and Comparative Example 1 are shown in Table 1.
[0058] Table 1: Expansion ratio of negative electrode sheets of Examples 1-2 and Comparative Example 1.
[0059] Expansion rate Example 1 21% Example 2 23% Comparative Example 1 43%
[0060] Please refer to Table 1. Compared with Comparative Example 1, the expansion rate of the negative electrode sheet of Example 1-2 is significantly reduced, indicating that the network structure formed by the titanium dioxide fiber can effectively alleviate this expansion, and the nanopore structure of the porous graphene can provide sufficient buffer space for the volume expansion of the silicon material during the charging and discharging process, thereby effectively reducing the expansion rate of the silicon-carbon negative electrode material, maintaining the stability of the electrode structure, and extending the service life.
[0061] The above are only implementation modes of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: include: Selecting a nanoscale coating material, wherein the coating material includes at least one of carbon dioxide fiber, aluminum oxide fiber and silicon nitride fiber; The coating material is uniformly coated on the surface of the pre-configured silicon-carbon negative electrode material by chemical vapor deposition to obtain a preliminary silicon-carbon negative electrode material with a network structure; Porous graphene is added to the preliminary silicon-carbon negative electrode material, and through physical mixing treatment and heat treatment, the porous graphene is evenly distributed inside and on the surface of the preliminary silicon-carbon negative electrode material to obtain an optimized silicon-carbon negative electrode material, wherein the pore size of the porous graphene is 10nm-50nm.
2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The step of uniformly coating the coating material on the surface of the pre-configured silicon-carbon negative electrode material by chemical vapor deposition to obtain a preliminary silicon-carbon negative electrode material having a network structure comprises: Performing drying pretreatment on the preconfigured silicon-carbon negative electrode material; The coating material and the pre-dried silicon-carbon negative electrode material are subjected to a chemical vapor deposition reaction to obtain a preliminary silicon-carbon negative electrode material having a network structure; The preliminary silicon-carbon negative electrode material is post-processed.
3. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The drying temperature of the drying pretreatment is 100°C and the drying time is 7 hours; the reaction temperature of the chemical vapor deposition reaction is 400°C and the reaction time is 2-5 hours; the post-treatment is: maintaining at a temperature of 500°C for 3-5 hours.
4. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In the step of adding porous graphene to the preliminary silicon-carbon negative electrode material, and uniformly distributing the porous graphene inside and on the surface of the preliminary silicon-carbon negative electrode material through physical mixing treatment and heat treatment to obtain an optimized silicon-carbon negative electrode material, the heat treatment is: in an inert atmosphere, placing the mixture obtained by physical mixing treatment at a temperature of 500°C-800°C and reacting for 6-8 hours.
5. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: Relative to the mass of the silicon-carbon negative electrode material, the mass of the coating material is 0.5wt%-1.0wt%, and the mass of the porous graphene is 10wt%-15wt%.
6. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The average diameter of the coating material is 50nm-500nm.
7. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The thickness of the network structure is 50nm-100nm, the network structure has pores, and the pore size of the porous graphene is smaller than the pore size of the pores.
8. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material is prepared by the method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 7.
9. A negative electrode sheet, characterized in that: Contains the silicon-carbon negative electrode material as described in any one of claim 8.
10. A battery, characterized in that: Contains the negative electrode sheet as claimed in claim 9.
